Impact of COVID-19 pandemic on the PREDIMED-Plus randomized clinical trial: Effects on the interventions, participants follow-up, and adiposity - Paz-Graniel, Indira; Fitó, Montserrat; Ros, Emilio; Buil-Cosiales, Pilar; Corella, Dolores; Babio, Nancy; Martínez, J. Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al. (Frontiers in Nutrition, 2023)
Background The COVID-19 pandemic has affected the implementation of most ongoing clinical trials worldwide including the PREDIMED-Plus study. The PREDIMED-Plus is an ongoing, multicenter, controlled intervention trial, aimed at weight-loss and cardiovascular disease prevention, in which participants were randomized (1:1 ratio) to an intervention group (energy-reduced Mediterranean diet, promotion of physical activity, and behavioral support) or to a control group (Mediterranean diet with usual care advice). When the pandemic began, the trial was in the midst of the planned intervention. The objective of this report was to examine the effects of the pandemic on the delivery of the intervention and to describe the strategies established to mitigate the possible adverse effects of the pandemic lockdown on data collection and adiposity. Methods We assessed the integrity of the PREDIMED-Plus trial during 5 identified periods of the COVID-19 pandemic determined according to restrictions dictated by the Spanish government authorities. A standardized questionnaire was delivered to each of the 23 PREDIMED-Plus recruiting centers to collected data regarding the trial integrity. The effect of the restrictions on intervention components (diet, physical activity) was evaluated with data obtained in the three identified lockdown phases: pre lockdown, lockdown proper, and post lockdown. Results During the lockdown (March/2020-June/2021), 4,612 participants (48% women, mean age 65y) attended pre-specified yearly follow-up visits to receive lifestyle recommendations and obtain adiposity measures. The overall mean (SD) of the proportions reported by each center showed that 40.4% (25.4) participants had in-person visits, 39.8% (18.2) participants were contacted by telephone and 35% (26.3) by electronic means. Participants’ follow-up and data collection rates increased across lockdown periods (from ≈10% at onset to ≈80% at the end). Compared to pre-lockdown, waist circumference increased during (0.75 cm [95% CI: 0.60–0.91]) and after (0.72 cm [95% CI: 0.56–0.89]) lockdown. Body weight did not change during lockdown (0.01 kg [95% CI: –0.10 to 0.13) and decreased after lockdown (-0.17 kg [95% CI: –0.30 to –0.04]). Conclusion Mitigating strategies to enforce the intervention and patient’s follow-up during lockdown have been successful in preserving the integrity of the trial and ensuring its continuation, with minor effects on adiposity. Clinical trial registration https://doi.org/10.1186/ISRCTN89898870, identifier ISRCTN89898870.